Switchable zero-bias anomaly in individual C60 molecules contacted with tunable aluminum electrodes - Scheer, E.; Böhler, T.; Edtbauer, A.; Egle, S.; Erbe, A.; Pietsch, T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We report the observation of strong resonances at zero bias in the differential conductance through Al–C60–Al junctions with tunable electrode distance, measured above T = 10 K. The conductance value at resonance ranges from a few percent up to eighty percent of the quantum of conductance. The resonances may disappear or reoccur completely and discontinuously upon very small changes of the electrode distance. However, once they are formed they are very robust with respect to changes of the electrode distance. We discuss similarities and differences to the common theories of the Kondo screening of a spontaneous spin polarization of the C60 molecule. We deduce Kondo temperatures in the range from 35 to 160 K and demonstrate that the temperature dependence is in agreement with the scaling behavior of the Kondo effect in the temperature range of our experiment.